2013
DOI: 10.7243/2050-0866-2-22
|View full text |Cite
|
Sign up to set email alerts
|

Impaired lipid transport in gestational diabetes mellitus

Abstract: Background: Gestational diabetes mellitus (GDM) complicates 5-6% of pregnancies, placing affected individuals at higher risk for pregnancy-related complications and persistent metabolic and cardiovascular disorders later in life. In this study, we evaluated the association between apolipoproteins and plasma cholesterol levels in patients with gestational diabetes compared to uncomplicated controls over the course of pregnancy. Methods: Plasma was prospectively collected from 311 nulligravid women during 3 time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
(21 reference statements)
1
3
0
Order By: Relevance
“…Apolipoprotein CIII was identified as candidate biomarkers in the maternal circulation at 16 to 20 wk in women with subsequently developed GDM . Plasma concentrations of Apo A‐II were observed to be increased from 4–12 wk to 24–28 wk in GDM patients . Two apolipoproteins (apos), APOA5 and APOE, were found to be increased in women with subsequently developed GDM in this study, supporting the view that impaired lipid transport and homeostasis play a role in GDM.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Apolipoprotein CIII was identified as candidate biomarkers in the maternal circulation at 16 to 20 wk in women with subsequently developed GDM . Plasma concentrations of Apo A‐II were observed to be increased from 4–12 wk to 24–28 wk in GDM patients . Two apolipoproteins (apos), APOA5 and APOE, were found to be increased in women with subsequently developed GDM in this study, supporting the view that impaired lipid transport and homeostasis play a role in GDM.…”
Section: Discussionsupporting
confidence: 76%
“…Most of them include blood coagulation, inflammatory response, immune response, complement activation, oxidative stress, etc. Interestingly, these processes have previously been linked to the pathophysiology of GDM , and thus the proteins can be considered as candidate biomarkers for screening and diagnosis of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the levels of three proteins, that is, APOA5, APOE, and PON1 and the other three proteins (APOC3, APOE, and PON1) associated with cholesterol efflux were found to be significantly higher in the serum of pregnant women who subsequently developed GDM and pregnant women with GDM, respectively. Previous studies showed that APO A‐II, APOC3, APOA5, APOE, and PON1 might serve as candidate biomarkers of GDM. These results support a role for impaired lipid transport in GDM and suggest a potential prediction and diagnosis of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that in patients with poorly controlled GDM, higher concentrations of high-density lipoproteins and higher triglyceride levels were detected in the third trimester, and the second and third trimesters, respectively. Another study suggested that APOA-II, APOC3 [19], APOE and PON1 [9] might be candidate biomarkers for GDM. Consistent with the above studies, we observed signi cantly higher levels of apolipoproteins APOE and APOC3 in the serum of GDM pregnant women.…”
Section: Discussionmentioning
confidence: 99%